Kinerja Pegawai Melalui Kompetensi Kerja Pada Pegawai Puskesmas Kambang Kabupaten Pesisir - Chintya Ones Charli; Dina Novira; Fadila Nanda Putri; Nesha Maharani (CV. ITTC INDONESIA, 2024)
This research aims to examine the influence of work experience and training on employee performance with work competency as an intervening variable using primary data obtained by distributing questionnaires to 55 employees as respondents, namely employees of the Kambang Health Center, Pesisir Selatan Regency. In this research, Structrual Equation Modeling (SEM) analysis tools were used using Partial Least Square (PLS). The results of the research show that there is a positive and significant influence of work experience on work competency, there is a positive and not significant influence of training on job competency, there is a positive and not significant influence of work experience on employee performance, there is a positive and significant influence of training on employee performance, there is an influence There is a positive and significant influence of Job Competency on Employee Performance. There is a positive and significant influence of Work Experience on Employee Performance through Job Competency. There is a positive and insignificant influence of Training on Employee Performance through Job Competency.